Performance of Private Retirement Scheme in Malaysia - Tai, Teh Lian; Sapuan, Noraina Mazuin; Hook, Law Siong (International Journal of Psychosocial Rehabilitation, 2020)
The world is aging, and Malaysia, too, does not escape from this phenomenon. The statistic of poor elderly in Malaysia had shown an increasing trend and many studies established a positive relationship between age and poverty. Various findings had shown Malaysia Employees Provident Fund alone is not enough to ensure a decent retirement period for Malaysian retirees. Private Retirement Scheme was identified as complementary retirement saving to the Employees Provident Fund. Ideally, Private Retirement Scheme will support retirement sufficiently and sustainably in Malaysia. However, the current situation showed indications of uncertainty and low return from the Private Retirement Scheme investment. Therefore, this research aims to investigate the performance of the Private Retirement Scheme in Malaysia since its’ inception from 2012 until 2018. There is limited research particularly done on the performance of the Private Retirement Scheme since it was newly introduced in 2012. There is also still a lack of historical performance until recently. Hence, it is about time to find out the performance of the Private Retirement Scheme after being seven years in the market, empirically. This study will employ the Capital Asset Pricing Model (CAPM) using the Sharpe and Treynor Ratio to calculate the performance of the Private Retirement Scheme. Previous results showed that the performance of investments has a significant and positive relationship with the investment rate. Thus, performance is a critical factor to encourage saving for retirement. This research found that Private Retirement Scheme performance in Malaysia since its inception until 2018 is low and unsatisfactory.